Reciprocal Effects of Oxidative Stress on Heme Oxygenase Expression and Activity Contributes to Reno-Vascular Abnormalities in EC-SOD Knockout Mice. (12th January 2012) - Kawakami, Tomoko; Puri, Nitin; Sodhi, Komal; Bellner, Lars; Takahashi, Toru; Morita, Kiyoshi; Rezzani, Rita; Oury, Tim D.; Abraham, Nader G.
Abstract : Heme oxygenase (HO) system is one of the key regulators of cellular redox homeostasis which responds to oxidative stress (ROS) via HO-1 induction. However, recent reports have suggested an inhibitory effect of ROS on HO activity. In light of these conflicting reports, this study was designed to evaluate effects of chronic oxidative stress on HO system and its role in contributing towards patho-physiological abnormalities observed in extracellular superoxide dismutase (EC-SOD, SOD3) KO animals. Experiments were performed in WT and EC-SOD (−/−) mice treated with and without HO inducer, cobalt protoporphyrin (CoPP). EC-SOD (−/−) mice exhibited oxidative stress, renal histopathological abnormalities, elevated blood pressure, impaired endothelial function, reduced p-eNOS, p-AKT and increased HO-1 expression; although, HO activity was significantly (P < 0.05 ) attenuated along with attenuation of serum adiponectin and vascular epoxide levels (P < 0.05 ). CoPP, in EC-SOD (−/−) mice, enhanced HO activity (P < 0.05 ) and reversed aforementioned pathophysiological abnormalities along with restoration of vascular EET, p-eNOS, p-AKT and serum adiponectin levels in these animals. Taken together our results implicate a causative role of insufficient activation of heme-HO-adiponectin system in pathophysiological abnormalities observed in animal models of chronic oxidative stress such as EC-SOD (−/−) mice.